Identification of the Mismatch Negativity in the Responses of Individual Listeners - Dalebout, Susan D.; Fox, Lisa G. (Journal of the American Academy of Audiology, 2000)
The mismatch negativity (MMN) was recorded from normal adults in three stimulus conditions: two contrast conditions and a control condition in which standard and deviant stimuli were identical. Averaged waveforms were analyzed by examiners blind to the evoking stimulus condition. Hit rates, a false alarm rate, and d values were determined based on the number of MMNs identified in each condition. Hit rates were low and the false alarm rate was relatively high, resulting in unacceptably small d values. The relationship between MMN findings and corresponding behavioral discrimination data for individual listeners was not systematic. Factors that may contribute to ambiguity and error in MMN data analysis are discussed.Abbreviations: ABR = auditory brainstem response, Cz = vertex, Fz = 30 percent of the distance between nasion and inion at the midline, MLR = middle latency response, MMN = mismatch negativity, SNR = signal-to-noise ratio
Keywords: Auditory evoked potentials; central auditory processing; mismatch negativity